Depletion of regulatory T cells in a hapten‐induced inflammation model results in prolonged and increased inflammation driven by T cells. (March 2015) - Christensen, A. D.; Skov, S.; Kvist, P. H.; Haase, C.
Summary Regulatory T cells (Tregs) are known to play an immunosuppressive role in the response of contact hypersensitivity (CHS), but neither the dynamics of Tregs during the CHS response nor the exaggerated inflammatory response after depletion of Tregs has been characterized in detail. In this study we show that the number of Tregs in the challenged tissue peak at the same time as the ear‐swelling reaches its maximum on day 1 after challenge, whereas the number of Tregs in the draining lymph nodes peaks at day 2. As expected, depletion of Tregs by injection of a monoclonal antibody to CD25 prior to sensitization led to a prolonged and sustained inflammatory response which was dependent upon CD8 T cells, and co‐stimulatory blockade with cytotoxic T lymphocyte antigen‐4‐immunoglobulin (CTLA‐4‐Ig) suppressed the exaggerated inflammation. In contrast, blockade of the interleukin (IL)‐10‐receptor (IL‐10R) did not further increase the exaggerated inflammatory response in the Treg‐depleted mice. In the absence of Tregs, the response changed from a mainly acute reaction with heavy infiltration of neutrophils to a sustained response with more chronic characteristics (fewer neutrophils and dominated by macrophages). Furthermore, depletion of Tregs enhanced the release of cytokines and chemokines locally in the inflamed ear and augmented serum levels of the systemic inflammatory mediators serum amyloid (SAP) and haptoglobin early in the response.